Disrupting Data: Developing Technology Integrated Assignments to Teach about Race and Racism - Rosa, Vanessa; Pinto, Caro (Radical Teacher, 2023)
Drawing on the lineage of liberatory pedagogy and critical information literacy, Professor Vanessa Rosa and research librarian Caro Pinto created the Disrupting Data Project. While teaching about race and inequality in higher education can be a challenging endeavor, Disrupting Data allowed the authors to encourage students to both think critically about the role of “data” in the history of race science alongside the perceived value of data science, data visualization, and data-driven decision making to challenge the notion that data is neutral or objective. This reflective essay focuses on the collaborative development process, different possibilities for engaging with students about the histories of race and racism, as well as the importance of creating and supporting collaborative learning spaces. The authors shed light on how equitable and collaborative partnerships can decenter hierarchies and positivist learning frameworks in higher education within the United States.